Socio-Aesthetic Realignment and Regional Heroism: Tracing the Resonance of Aceh’s Cultural Identity in the Poetics of Angkatan 45 - Sheshilia Putri Damanik; Rosmawaty Harahap (Journal of Aceh Studies, 2026)
The emergence of Angkatan 45 (the Generation of 1945) marks a critical milestone in the evolutionary trajectory of modern Indonesian literature, characterized by a radical departure from colonial and classical aesthetic constraints. While mainstream literary histories frequently examine this linguistic revolution through a centralized, macro-national lens, few studies investigate how regional identities, specifically the sociopolitical and cultural landscape of Aceh, intersected with this structural transformation. This study investigates the distinct poetic characteristics, philosophical conceptions, and structural dynamics of Angkatan 45 poetry by contextualizing its development within the historical consciousness and resilient cultural framework of Acehnese society during the revolutionary period. Employing a qualitative descriptive research design integrated with a critical historiographical review and micro-level structural textual analysis, this research analyzes the dual ideological pillars of Expressionism and Realism across selected poetic texts and the cultural manifesto of the Surat Kepercayaan Gelanggang. The findings reveal that the aesthetic deconstruction enacted by Angkatan 45, characterized by raw syntactic economy and colloquial diction, was deeply informed by peripheral struggles, where regional cultural symbols and islamic humanism served as vitalist markers of anti-colonial defiance. Ultimately, this paper highlights the pedagogical and socio-cultural value of preserving this decentralized literary genealogy, demonstrating how a period of intense high-stakes crisis successfully revolutionized the linguistic, semantic, and inclusive fabric of modern Indonesian discourse while preserving local cultural sovereignty.